2007
DOI: 10.1016/j.bbrc.2007.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor-induced phosphorylation of STAP-2 on tyrosine-250 is involved in its STAT3-enhancing activity

Abstract: Signal transducing adaptor protein-2 (STAP-2) is a recently identified adaptor protein that contains Pleckstrin and Src homology 2 (SH2)-like domains as well as a YXXQ motif in its C-terminal region. Our previous studies revealed that STAP-2 binds to signal transducer and activator of transcription 3 (STAT3) and STAT5, and regulates their signaling pathways. In the present study, we identified tyrosine-250 (Tyr250) in STAP-2 as a major site of phosphorylation by v-Src and Jak2, using a phospho-specific antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Anti-STAP-2 antibody was purchased from Everest Biotech (Oxfordshire, UK). Anti-phosphoSTAP-2 Tyr250 was prepared as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-STAP-2 antibody was purchased from Everest Biotech (Oxfordshire, UK). Anti-phosphoSTAP-2 Tyr250 was prepared as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…To further probe the phosphorylation status of STAP-2 Tyr250, we also used a phosphospecific antibody against the Tyr250 site, designated anti-pSTAP-2 Tyr250, as described previously [14]. Myc-tagged wild-type STAP-2 (STAP-2 WT) or a series of STAP-2 YF mutants were expressed with or without Brk in 293T cells.…”
Section: Brk Phosphorylates Stap-2 At Tyr250mentioning
confidence: 99%
“…Expression vectors, c-Fms, epitope-tagged STAP-2 and its YF (substitution of Tyr to Phe) mutants were described previously [11,13,16]. Antibody against c-Fms, ERK1, and GST antibodies were obtained from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Previously, we have shown that STAP-2 shows the characteristics of an adaptor protein that can interact with several other signaling molecules and that it regulates a variety of signaling pathways. However, only tyrosine-phosphorylation of STAP-2 has been demonstrated to modulate its functions [14]. In this study, we demonstrated, for the first time, a mechanism that regulates STAP-2 activity through Cbl-mediated proteasome-dependent degradation.…”
Section: Discussionmentioning
confidence: 68%
“…Human embryonic kidney carcinoma cell line 293T, human hepatoma cell line Hep3B and human cervix carcinoma cell line HeLa were maintained in DMEM containing 10% FCS. Stable transformants expressing Myc-tagged STAP-2 in Jurkat [3], HeLa [13] and Hep3B [14] were established as described previously and maintained in the above medium in the presence of G418 (0.5 mg/ml). 293T was transfected by the standard calcium precipitation protocol.…”
Section: Cell Culture Transfection and Luciferase Assaysmentioning
confidence: 99%